Tissue-Specific Factors Differentially Regulate the Expression of Antigen-Processing Enzymes During Dendritic Cell Ontogeny - Mahiddine, Karim; Hassel, Chervin; Murat, Claire; Girard, Maeva; Guerder, Sylvie (Frontiers in Immunology, 2020)
Dendritic cells (DCs) form a collection of antigen-presenting cells (APCs) that are distributed throughout the body. Conventional DCs (cDCs), which include the cDC1 and cDC2 subsets, and plasmacytoid DCs (pDCs) constitute the two major ontogenically distinct DC populations. The pDCs complete their differentiation in the bone marrow (BM), whereas the cDC subsets derive from pre-committed BM precursors, the pre-cDC, that seed lymphoid and non-lymphoid tissues where they further differentiate into mature cDC1 and cDC2. Within different tissues, cDCs express distinct phenotype and function. Notably, cDCs in the thymus are exquisitely efficient at processing and presenting antigens in the class II pathway, whereas in the spleen they do so only upon maturation induced by danger signals. To appraise this functional heterogeneity, we examined the regulation of the expression of distinct antigen-processing enzymes during DC ontogeny. We analyzed the expression of cathepsin S (CTSS), cathepsin L (CTSL), and thymus-specific serine protease (TSSP), three major antigen-processing enzymes regulating class II presentation in cDC, by DC BM precursors and immature and mature cDCs from the spleen and thymus. We found that pre-cDCs in the BM express relatively high levels of these different proteases. Then, their expression is modulated in a tissue-specific and subset-specific manner with immature and mature thymic cDCs expressing overall higher levels than immature splenic cDCs. On the other hand, the TSSP expression level is selectively down-regulated in spleen pDCs, whereas CTSS and CTSL are both increased in thymic and splenic pDCs. Hence, tissue-specific factors program the expression levels of these different proteases during DC differentiation, thus conferring tissue-specific function to the different DC subsets.